A necrobiopolítica, a espetacularização midiática e a execução de Lázaro Barbosa na legitimação discursiva do homicídio institucionalizado - Gomes, Davi Hipólito (2024)
This dissertation addresses the issue of legitimizing institutionalized homicide, from the perspective of necrobiopolitics, and the influence of the media during the hunt and execution of Lázaro Barbosa, an emblematic case that aroused great public attention and raised important questions about the role of the State and the society in perpetuating violence against certain individuals. A priori, through theory related to Foucault's discursive studies, we sought to systematize the relationship between discourse, power and knowledge in Michel Foucault. Through the discursive analysis provided by the concept of necrobiopolitics, we explore how the power structures of the State and security institutions can transform the management of life at the population level into the management of death, legitimizing violent actions against marginalized groups. It examines how the marginalization of Lázaro Barbosa, an individual accused of crimes, became a pretext for the practice of institutionalized homicide, in which the State's lethal action is justified as a means of "protecting" society. Our research also analyzes the role of the media during the hunt for Lázaro Barbosa, exploring how the spectacularization and sensationalization of events can influence public perception, contributing to the legitimization of institutionalized homicide. We investigated how media coverage can create stigmatizing and dehumanizing statements, leading to the hardening of public discourse and the acceptance of extreme actions by security institutions. Through case studies, news analyzes and media discourses, we seek to identify patterns of discursive construction that influence the public's perception of the figure of Lázaro Barbosa, reinforcing the idea of danger and threat and justifying state violence as an appropriate response. We proposed a discursive analysis of media statements, seeking to understand how they can contribute to the legitimization of institutionalized homicide and to the maintenance of power structures that perpetuate necrobiopolitics. Finally, we conclude with reflections on the role of society in deconstructing these necrobiopolitical practices, highlighting the importance of public awareness, questioning media statements and political engagement in the fight against institutionalized violence. We proposed a call to action to promote social justice, equality and human dignity, aiming to build a society that fights for collective rights and rejects behaviors that perpetuate inequalities that define who should live and who can die. We believe in a resistance that may demand, from the spectator population, counter-conducts capable of nullifying attempts to legitimize institutionalized homicide.